The Effect of Differentiated Instruction and Learning Motivation on Elementary School Students’ Learning Outcomes - Rahmah; Sudi Dul Aji; Dwi Fauzia Putra (South Sulawesi Education Development (SSED), 2026)
This study aimed to examine the effect of differentiated instruction and learning motivation on elementary school students’ learning outcomes in Natural and Social Sciences (IPAS), within the context of instructional practices aligned with the principles of the Merdeka Curriculum. A quantitative quasi-experimental design with a 2×2 factorial model was employed to analyze the main and interaction effects of instructional approach and learning motivation. The participants were 46 sixth-grade students from two elementary schools, consisting of an experimental group taught using differentiated instruction and a control group taught using conventional instructional methods. Data were collected through a learning outcomes test and a learning motivation questionnaire and analyzed using Two-Way ANOVA at a significance level of 0.05. The results indicated that students who received differentiated instruction achieved significantly higher learning outcomes than those who received conventional instruction. Learning motivation also had a significant effect, with highly motivated students demonstrating better academic achievement. However, no significant interaction effect was found between instructional approach and learning motivation, suggesting that differentiated instruction is more effective in improving learning outcomes regardless of students’ motivation levels. These findings provide empirical evidence supporting the implementation of differentiated instruction in IPAS learning at the elementary school level.